2017
DOI: 10.18699/vj17.305
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory transport efficiency of the amorphous and crystalline manganese oxide nanoparticles

Abstract: The ability to deliver particulated xenobiotics and therapeutic drugs directly from the nasal cavity to the central nervous system, bypassing the hemato-encephalic barrier, determines a high importance of investigation of factors influencing this process. It was shown that the bioavailability of solid particles is influenced by their size and surface charge. At the same time, the impact of a crystal structure (crystalline/amorphous) has been poorly investigated. In this study, using sexually mature male C57BL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…As shown in our previous work, relaxation values (R1, ms -1 , see Fig. 1, c) of Mn 3 O 4 -NPs correlate with manganese concentration in the samples (Romashchenko et al, 2017). In vivo experiments showed that the amplitude of the MRI signal in OB 12 hours after the intranasal application of Mn 3 O 4 -NPs was directly proportional to the manganese concentration in the tissue (Romashchenko et al, 2017).…”
Section: Methodssupporting
confidence: 74%
See 4 more Smart Citations
“…As shown in our previous work, relaxation values (R1, ms -1 , see Fig. 1, c) of Mn 3 O 4 -NPs correlate with manganese concentration in the samples (Romashchenko et al, 2017). In vivo experiments showed that the amplitude of the MRI signal in OB 12 hours after the intranasal application of Mn 3 O 4 -NPs was directly proportional to the manganese concentration in the tissue (Romashchenko et al, 2017).…”
Section: Methodssupporting
confidence: 74%
“…OB were taken for calibration, since the concentration of nanoparticles after the intranasal or inhalation administration is the highest in this region (Moshkin et al, 2014). Earlier, we demonstrated low solubility of Mn 3 O 4 -NPs at different pH (4-7), which entitled us to regard the observed changes in the MRI signal in mouse brain divisions after intranasal/intravenous administration of Mn 3 O 4 -NPs as a result of accumulation of insoluble manganese rather than Mn 2+ in the nervous tissue (Romashchenko et al, 2017) and use the level of the T1-weighted MRI signal to assess NP accumulation in the tissue.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations